Rethinking Wildlife in Your Florida-Friendly Edible Landscape - Tina McIntyre; Hamutahl Cohen; Rachel Gutner; Tiare Silvasy; Esen Momol (EDIS)
Considering wildlife in your edible landscape can be a complex challenge. Although wild animals can cause crop damage, this may not be a conflict that has to be addressed. This new 5-page publication of the UF/IFAS Environmental Horticulture Department provides a useful decision tree that helps users make choices regarding the species in their managed area. Our goal is to help the gardener become more accepting of wildlife among edible crops and coexist in a shared environment. Written by Tina McIntyre, Hamutahl Cohen, Rachel Gutner, Tiare Silvasy, and Esen Momol. https://edis.ifas.ufl.edu/ep630